2019
DOI: 10.1042/bsr20190019
|View full text |Cite
|
Sign up to set email alerts
|

Identification of core genes and clinical roles in pregnancy-associated breast cancer based on integrated analysis of different microarray profile datasets

Abstract: More women are delaying child-birth. Thus, the diagnosis of pregnancy-associated breast cancer (PABC) will continue to increase. The aim of this study was to identify core candidate genes of PABC, and the relevance of the genes on the prognosis of PABC. GSE31192 and GSE53031 microarray profile datasets were downloaded from the Gene Expression Omnibus database and differentially expressed genes were analyzed using the R package and GEO2R tool. Then, Gene Ontology and Kyoto Encyclopedia of Gene and Genome pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…The search strategy retrieved 23 articles. Of these, 16 were omitted based on the exclusion criteria and 7 were eligible (11)(12)(13)(14)(15)(16)(17). While examining the references of eligible articles, 2 more articles were included (18,19).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search strategy retrieved 23 articles. Of these, 16 were omitted based on the exclusion criteria and 7 were eligible (11)(12)(13)(14)(15)(16)(17). While examining the references of eligible articles, 2 more articles were included (18,19).…”
Section: Resultsmentioning
confidence: 99%
“…As far as the genomic analysis approach is concerned, four studies were based on formalin-fixed paraffin embedded (FFPE) tissue analysis ( 11 13 , 18 ), one study examined fresh frozen tissue ( 14 ), three studies were associated with bioinformatic analysis and microarray profile datasets ( 15 , 16 , 19 ), and one study did not provide precise information regarding the methodology steps ( 17 ). Importantly, all studies included in the review were case-control studies; thus, the groups compared in each study exhibited similar clinicopathological characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ARF3 overexpression promotes breast cancer cell proliferation by regulating the cellcycle G1/S transition, through inhibition of FOXO1 transcription factor activity . Additionally, ARF3 was found to be a candidate gene involved in the progression of Olstad et al, 2003;Ma et al, 2005;Kannangai et al, 2007;Tsai et al, 2012;Schlienger et al, 2015;Davis et al, 2016;Gu et al, Woo et al, 2009;Bidkhori et al, 2013;Howley et al, 2018;Wu Q. et al, 2018ARF6 ↑ Breast, Gastric, Glioma, Liver, Lung, Melanoma, Pancreatic, Prostate, Renal Cell Carcinoma Hashimoto et al, 2004Hu et al, 2009;Knizhnik et al, 2011;Oka et al, 2014;Morgan et al, 2015;Zhang et al, 2015;Hashimoto et al, 2016;Liang et al, 2017; Fujii et al, 2014;Guo et al, 2015;Fujii et al, 2016;Hu et al, 2018;Chen et al, 2019;Harada et al, 2019;Isono et al, Calin et al, 2005;Petrocca et al, 2006;Yendamuri et al, 2008;Siltanen et al, pregnancy-associated breast cancer, based on integrated analysis of microarray profile datasets (Zhang et al, 2019).…”
Section: Arf3mentioning
confidence: 99%
“…Similarly, low expression of FBXO22 is associated with poor survival in patients with breast cancer 42 . Intriguingly, FBXO22 is downregulated in pregnancy-associated breast cancer via analysis of NCBI-GEO datasets 51 . IHC analysis in renal cell carcinoma (RCC) tissues found that FBXO22 expression levels were decreased in RCC specimens compared with those in normal renal tissues 50 .…”
Section: Fbxo22 Expression In Human Tumor Tissuesmentioning
confidence: 99%